2015
DOI: 10.1007/s12651-015-0188-3
|View full text |Cite
|
Sign up to set email alerts
|

The future of the German industrial relations model

Abstract: The paper examines recent evidence on the erosion of the German industrial relations model. Although its coverage has declined, much of this has occurred in smaller and newer establishments, and compared with Britain, it has remained solid in the areas of Germany's traditional industrial strength. This is explained by the nature of high performance work systems that involve flexible working and on-the-job problem-solving. Both countries have modernised their work systems in recent decades, with German industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
(46 reference statements)
0
17
0
Order By: Relevance
“…Even if this swan song may be a little bit premature since we have shown that the traditional German IR model still does exist in some places, the model is clearly on the retreat and the outlook is rather bleak. It is an open question how far the erosion and segmentalism can go before undermining social cohesion and the political stability of the entire corporatist German model (Marsden 2015). Although most observers seem to take a prolongation of the weakening of collective regulation and its actors for granted, in particular if there is insufficient government support for the system (as argued by Streeck 2016), Haipeter (2013) also sees some signs of renewal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if this swan song may be a little bit premature since we have shown that the traditional German IR model still does exist in some places, the model is clearly on the retreat and the outlook is rather bleak. It is an open question how far the erosion and segmentalism can go before undermining social cohesion and the political stability of the entire corporatist German model (Marsden 2015). Although most observers seem to take a prolongation of the weakening of collective regulation and its actors for granted, in particular if there is insufficient government support for the system (as argued by Streeck 2016), Haipeter (2013) also sees some signs of renewal.…”
Section: Discussionmentioning
confidence: 99%
“…2 Additional important aspects of the German IR model mentioned in the literature include the importance of the law and the intermediary character of works councils and trade unions (Jacobi et al 1998), skill formation via vocational training (Marsden 2015), and typical outcomes like relatively low wage dispersion and income inequality (Streeck 2016). Whereas the present paper only focuses on the German IR system or model, the term "German model" has also been used more broadly to describe the configuration of the German social and economic system (for a historical and critical discussion, see Streeck 2009: 108ff.…”
Section: Introductionmentioning
confidence: 99%
“…), and work has become overall more standardised and routinized during the nineties (Springer ). In his recent analysis of the survey of the European Working Conditions Observatory, Marsden () found that the work organization in around 65 per cent of German firms does not include job discretion, autonomy and problem‐solving (even though the rate is still low compared to the UK).…”
Section: The Role Of Skills Industrial Relations and Work Organizatimentioning
confidence: 99%
“…It has recently been argued that the continuing endurance of the German model owes much to trust. In particular, Marsden (2015) contends that this is underscored by the presence in some but by no means all sectors of a high-discretion learning model of work organization, which he contrasts with the more managerial-directed lean model in Britain. He claims that German manufacturers have been successful in repositioning themselves within international supply chains (and the so-called trade in tasks) as reflected in a rising share of exports in manufacturing gross value added.…”
Section: Exhibit 1 Micro Foundations Of Trust: the German Modelmentioning
confidence: 99%